Validation of Boron Analysis Method on SRM Tomato Leaves NIST No. 1573a using Fluorescence Spectrophotometry - Lailatusholihah, Isna; Tri Utami, Aisyiah Restu; Roto, Roto; Kuncaka, Agus (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The study of borax contamination on SRM Tomato Leaves NIST no. 1573a was succesfully analized. This study used sausage samples using Spectrophotometry Fluoresence method. Boron analysis by fluorescence spectrophotometry was done by excitation at 522 nm and emission at 593 nm. Validation method uses linear standard curve in the concentration range of 1-4.5 ppm with R2 = 0.9991. The sensitivity, limit of detection, limit of quantification, and percent recovery are 4695.7 a.u.ppm-1, 0.241±0,06 ppm, 0.805±0,06 ppm, and 92.8%, respectively. This means that determining boron using the borate ester distillation method with fluorescence spectrophotometry can be used as a new method for determining boron levels in food samples.